Currency Amounts in the SDR Basket : Proposed Changes to the Rounding Methodology. (Policy Papers; Policy Paper ;, 2016)
Currency amounts are used to determine the daily value of the SDR. Currency amounts are the number of units of each currency in the SDR basket. The value of the SDR (in U.S. dollars) is the sum of these amounts, valued at daily exchange rates of the currencies against the U.S. dollar. These currency amounts are determined on the last business day before the new SDR basket becomes effective (transition date) such that they correspond to the currency weights determined by the IMF Executive Board in the context of the SDR Review, and remain fixed over the SDR valuation period. To facilitate SDR users in adjusting their portfolios to the new basket, the IMF publishes illustrative currency amounts in the lead up to the transition date.